A retrospective study of comparison of collagen dressing versus conventional dressing for skin graft donor site - Dave, Tushar J.; C. A., Shashirekha; K., Krishnaprasad (International Surgery Journal, 2021)
Background: Split-skin grafting is commonly employed for covering skin defects in case of ulcers, deep burns and following trauma. It involves harvesting of the epidermis and upper 1/3rd of dermis resulting in a wound called donor site wound (DSW). These wounds pose a kind of burden to patients during the process and after the process of wound healing. These wounds tend to cause pain, are at risk of getting infected, pruritis and cosmetic inconvenience. DSW has been managed with closed or open dressings. Out of many methods, we aim to compare the efficacy of collagen dressing with that of conventional dressing in this study. Methods: A retrospective study including 30 subjects were stratified into 2 groups; group A-collagen dressing and group B- conventional dressing. Patients aged between 18 to 60 years undergoing split thickness skin grafting were included. Patients who are immunocompromised, diabetic, with underlying skin disease and infected wounds were excluded. The outcome was compared in terms of pain, pruritis and scar assessment using Vancouver scar scale. Results: In the present study there was significant difference in median pain score, pruritus and median Vancouver scar score in collagen group compared to conventional group at all the intervals. Also, the incidence of surgical site infection was lower in the collagen dressing group. Conclusions: Collagen dressing is superior compared to conventional dressing in terms of lower pain score, pruritus score and Vancouver scar score.